(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
The study was designed to investigate the influence of gender related factors on access to antiretroviral therapy. The results showed that the number of females visiting antiretroviral therapy clinics was twice that of males and in the 18-26 years age bracket, females were three times more affected by HIV/AIDS than males. The married carried a 5-fold risk of carrying the AIDS virus while women were twice as likely to be infected by their husbands as compared to men getting the virus from their wives. The findings indicate that the lower the formal education, the higher the chances of contracting the virus. The findings suggest men had a significant advantage over women on access to antiretrovirals. The clinic schedules precluded about 10% of the patients from access. Social stigma was low (about 10%) within spouses, and very high (about 90%) outside the institution of marriage. Women bore the larger burden of the stigma. In addition, the results suggest that gender segregated clinics would have no influence on the number of patients attending the clinics.